PENGARUH FORTIFIKASI NANOPARTIKEL KALSIUM LAKTAT KERABANG TELUR TERHADAP SIFAT KIMIA DAN FISIK BAKSO AYAM - Agus Hadi Prayitno (Buletin Peternakan, 2016)
The experiment was conducted to analysis the effect of nanoparticle eggshell calcium lactate fortification on chemical and physical properties of chicken meatballs. The materials were chicken meat, filler, spices, salt, eggshell calcium and nanoparticle calcium lactate. Fortification level of eggshell calcium and nanoparticle calcium lactate on making meatballs was 0.3% of the total meatball dough. Each treatment consisted of five replications. The data of chemical and physical properties of meatballs were analyzed statistically using variance analysis. The differences between means were tested by Duncan's new Multiple Ranges Test. The meatball fortified with eggshell calcium showed lower moisture content 67.92%, and showed higher fat content 6.92% and ash 2.56% than those of nanoparticle eggshell calcium lactate. The meatballs fortified with eggshell calcium had higher pH value 7.34 and water-holding capacity 58.53% and more firmness than those of fortified with eggshell calcium lactate. (Keywords: Chemical and physical properties, Chicken meatballs, Eggshell, Fortification, Nanoparticle calcium lactate)